Políticas de formação continuada das professoras de educação infantil do município de João Pessoa e suas implicações para a prática docente - Alves, Maria da Conceição Pereira Ferreira (2023)
This dissertation discusses about continuing education policies for Early Childhood Education teachers in the city of João Pessoa and its main objective is to investigate the incidence of current continuing education policies at national and local level, for Early Childhood Education teachers, and the impact of these on their teaching practices, in the municipality of João Pessoa-PB. Therefore, the specific objectives were: to analyze how national public policies that guide continuing education processes in the public sphere of Early Childhood Education are articulated with local policies; to understand how these policies guide the organization and functioning of continuing training proposals in Early Childhood Education promoted by the João Pessoa Municipal Education Network (RME/JP) and reflect on the consequences of these policies in the pedagogical contexts in which teachers work. To achieve these objectives, we chose the period from 2016 to 2022 as the time frame. The research was qualitative, and it was developed in three moments: 1) systematic review on the topic of continuing education for Early Childhood Education teachers; 2) documentary analysis, based on national and local policy proposals; 3) field research, through observation of the training processes of the year 2022 at RME/JP, and semi-structured interviews with ten (10) teachers who work in 04 (four) Municipal Early Childhood Education Centers (CMEIs), serving children from six months to five years and eleven months. The method adopted for this investigation was based on Historical-Cultural Theory, from a Vygotskyan perspective, considering Vygotsky's contributions in the field of teacher training. For data analysis, we used the Content Analysis technique, based on Bardin, to answer the questions of this research. The training processes were developed by foundations, private higher education institutions, which went through bidding processes, partnership with the federal government, partnership with the Federal University of Paraíba (UFPB), all of them presented weaknesses. The results indicate that there is an incidence of national and local policies, with little articulation between them.